KEBIJAKAN MODA TRANSPORTASI TRADISIONAL BECAK DALAM MENDUKUNG PARIWISATA DI DAERAH ISTIMEWA YOGYAKARTA - Wijaya, Ardi Bayu; Triputro, R Widodo (CV The Journal Publishing, 2025)
In line with the development of the increasingly modern era, the Special Region of Yogyakarta has developed by maintaining the cultural and historical values ​​it has as a regional identity. This identity makes the Special Region of Yogyakarta have a tourist attraction for both domestic and international tourists. One of the cultural heritages in the field of transportation that still exists in the Special Region of Yogyakarta is the traditional pedicab. In the era of rapid technological development, traditional pedicabs are still the main source of livelihood for most pedicab drivers. In realizing preservation efforts, traditional pedicabs are now used as an alternative means of transportation to support tourism. Efforts to preserve traditional pedicabs have been supported by regional regulations that also protect the existence of this transportation. In the regional tourism development plan, traditional pedicabs are used as alternative transportation that can support the tourism sector. The results of this study describe the policy of traditional pedicab transportation modes in supporting tourism along with supporting and inhibiting factors in implementing the policy.